Does Growth Enhancement Support Scheme (GESS) contribute to youth development in informal farm entrepreneurship? Evidence from rural communities in Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
Purpose - The purpose of this paper is to critically examine the impact of a growth enhancement support scheme (GESS) on youth development in informal farm entrepreneurship in Nigeria. Its special focus is to investigate the impact of the GESS on rural youths' adoption of new technologies needed to sustainably increase food security in Nigeria. Design/ methodology/ approach - This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially cross-sectional, describing and interpreting the current situation. A total of 800 rural youths were sampled across the six geopolitical zones of Nigeria. Findings - The result from the use of a bivariate probit model indicate that the GESS has a significant impact on rural youths' innovations in farming. Practical implication - This suggests that information and communication technology (ICT) could provide new opportunities for making farming more interesting and enterprising for rural young people. Social implication - It implies that while old male and female farmers are less likely to adopt the new farming technologies needed to achieve Nigeria's agricultural transformation agenda (ATA), a younger generation can help introduce new technologies, whilst also learning from traditional methods. Originality/ value - This research adds to the literature on informal farm entrepreneurship and rural communities' debate in developing countries. It concludes that engaging youths in GESS should form the foundation of the ATA in Nigeria, which, in turn, would offer adequate combination of new and traditional solutions to address the challenges of food insecurity in sub-Saharan Africa.
Keywords: 330; Youth Development Initiative; Informal Farm Entrepreneurship; GrowthEnhancement Support Scheme (GESS); Rural Communities in Nigeria